Relative Importance of Sex, Pre-Starvation Body Mass and Structural Body Size in the Determination of Exceptional Starvation Resistance of Anchomenus dorsalis (Coleoptera: Carabidae) - Knapp, Michal (PloS one, 2016)
In nature, almost all animals have to cope with periods of food shortage during their lifetimes. Starvation risks are especially high for carnivorous predatory species, which often experience long intervals between stochastic prey capturing events. A laboratory experiment using the common predatory carabid beetle Anchomenus dorsalis revealed an exceptional level of starvation resistance in this species: males survived up to 137 days and females up to 218 days without food at 20°C. Individual starvation resistance was strongly positively affected by pre-starvation body mass but only slightly by beetle structural body size per se. Females outperformed males even when the effect of gender was corrected for the effects of structural body size and pre-starvation body mass. The better performance of females compared to males and of beetles with higher relative pre-starvation body mass could be linked to higher fat content and lean dry mass before starvation, followed by a greater decrease in both during starvation. There was also a difference between the sexes in the extent of body mass changes both during ad libitum feeding and following starvation; the body masses of females fluctuated more compared to males. This study stresses the need to distinguish between body mass and structural body size when investigating the ecological and evolutionary consequences of body size. Investigation of the net effects of body size and sex is necessary to disentangle the causes of differences in individual performances in studies of species with significant sexual size dimorphism.
Keywords: fyziologická adaptace; Coleoptera; Animals; Lipids; Body Size; Body Weight; Longevity; Male; náhodné rozdělení; dlouhověkost; hladovění; mužské pohlaví; Female; velikost těla; predátorské chování; Adaptation, Physiological; Predatory Behavior; Sex Characteristics; tělesná hmotnost; pohlavní dimorfismus; Random Allocation; zvířata; lipidy; ženské pohlaví; brouci; Starvation